2020
DOI: 10.1177/2399808320919771
|View full text |Cite
|
Sign up to set email alerts
|

Validating activity, time, and space diversity as essential components of urban vitality

Abstract: Urbanization’s rapid progress presents an urgent challenge for developing a predictive, quantitative theory of “the death and life of cities” (a.k.a. “the essential diversity conditions for the urban built environment”). Despite the importance of activity diversity (i.e. serving different primary functions), existing works ignored that time diversity (i.e. attracting people at different times of the day) and space diversity (i.e. attracting people from different districts) also play important roles in promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 63 publications
(65 reference statements)
0
24
0
Order By: Relevance
“…Cellular signaling data, social media check-in data, smart-card records, and bike-sharing and taxi trajectory data are needed to estimate population distribution and mobility more accurately. Additionally, limited by our research framework, we did not consider time diversity, although studies have shown that time diversity has a strong association with urban vibrancy [ 21 ]. Future studies should strengthen the collection and acquisition of long-term continuous data to dynamically monitor and assess the relationship between the built environment and urban vibrancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cellular signaling data, social media check-in data, smart-card records, and bike-sharing and taxi trajectory data are needed to estimate population distribution and mobility more accurately. Additionally, limited by our research framework, we did not consider time diversity, although studies have shown that time diversity has a strong association with urban vibrancy [ 21 ]. Future studies should strengthen the collection and acquisition of long-term continuous data to dynamically monitor and assess the relationship between the built environment and urban vibrancy.…”
Section: Discussionmentioning
confidence: 99%
“…Through recent advances in ICT (information and communication technology) and spatial orientation technologies, especially location-based service technologies, lifestyles have been undergoing great changes, and massive amounts of microscale spatiotemporal geographical open data are now available. Various spatiotemporally tagged data, including cellular signaling data, social media check-in data, point-of-interest (POI) data, smart-card records, taxi trajectory data, SCB data, and street view data, have been widely used in urban planning, population prediction [ 26 , 27 ], socioeconomic development [ 28 , 29 ], and urban vibrancy research [ 21 ], and even to infer individual personality [ 30 ]. Meanwhile, this new data environment provides the possibility of capturing human activities, rhythms, and preferences on a massive scale [ 31 ], enabling us to portray and quantify vibrancy much more easily and more accurately.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu and Niu [2] have verified the influence of the built environment on UV using mobile phone location data in Shanghai, China. Furthermore, Kang, et al [12] studied the influence of activity, time, and space diversity on UV and concluded that the three together significantly impact UV.…”
Section: Introductionmentioning
confidence: 99%